Effectiveness of Local Clove Oil Formula on Some Pathogenic Bacteria and Muscle Spasms - Fouad H. Kamel; Hemn Kareem Qadir; Mahabad Mohammed Hussein (Institute of Medico-legal Publications Pvt Ltd, 2021)
Samples of clove obtained from local baser in Erbil-Iraq to determine the potential antimicrobial, andapplicant as external physical potential analgesic action. The clove extracts were found to inhibit the growthof Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa. Extract of Cloves oil gotten andmixed with Olive oil with deferent ratios (1:1, 1:2, 1:3, 1:4, 1:5 and2:1) volumes clove oil: olive oil, andhomogenized to preparing the formulas. The prepared formulas were tested for healing and checked for anyadverse effects on 30 donors who presented with muscle spasms and pain. The best formula concentration(I: 5) Clove: Olive oils, confirmed 40% of healing in the first day and 100% of healing within three days ofapplying the formula for the donors, and show no adverse effect. Then the best formula was used to treat120 donors who presented with muscle spasms and muscle pain. and the result was fantastic as 40% of themcured after the first day of applying this formula and all (100%) of them cured within three days of usingthis formula without any adverse effect; while there were side effects recorded such as weakness, sleepiness,delirium and confusion: the positive group (control group) who used analgesic medications to relieve musclespasm under the supervision of a professional nurse; whereas the negative group (healthy individual) whoused this formula showed no side effects. This indicates that using the new prepared formula is healthier thanusing medications like analgesics in managing muscle spasms.